Drawings and digital graphics by Matija Rajković, Novi Sad, 2015, and Retrospective exhibition of Zoran Rajković in the Kruševac art gallery - Grković Biljana (Visoka škola strukovnih studija za vaspitače, Kruševac, 2015)
nema